The Relationship between Parenting Styles and Adolescents Social Development - Nurlela, Lela; Fajar Rinawati; Ari Susanti; Sukma Ayu Candra Kirana; Bagas Hadi Saputro (Journal Of Nursing Practice, 2026)
Background: The Relationship between Parenting Styles and Adolescent Social Development. Adolescent social development is the process of growing the ability to interact and understand social rules. Parenting styles play an important role in shaping children's attitudes and behavior in their social environment. This study aims to analyze the relationship between parenting styles and adolescent social development. Purpose: This study aims to analyze the relationship between parenting styles and adolescents’ social development. Methods: The research is a quantitative descriptive study with a cross-sectional approach. A sample of 165 students from class 11 at SMA Hang Tuah 5 Sidoarjo was selected using simple random sampling technique. The research was conducted on January 23-30, 2025. The questionnaire exploring Parenting styles were measured using the Parenting Styles and Dimensions Questionnaire-Short Version (PSDQ), and Adolescent Social Development Questionnaire (Rahmawati, 2021) for measured the social development. Data analysis used the Spearman rank correlation with alpha 5%. Results: The results showed that most parents applied democratic parenting styles (49.70%) and the majority of adolescents had fairly good social development (55.15%). The Spearman Rho test showed r = 0.323 with ρ = 0.01 (ρ < 0.05), indicating a weak relationship between parenting styles and adolescent social development. Conclusion: Adolescent social development does not always follow the same pattern because it is influenced by various factors, such as parenting styles, stimulation, health conditions, and child motivation. The ideal parenting style is one that balances supervision and freedom, supported by fulfilling needs and good communication. Therefore, parents are advised to apply a balanced parenting style to support optimal social development in adolescents.